PENGARUH KADAR LENGAS TANAH PADA BERBAGAI FASE PERTUMBUHAN TERHADAP PERTUMBUHAN DAN HASIL KEDELAI - Achmad Fatchul Aziez; Agus Budiyono; Endang Suprapti; Ari Kus Wardiyanto (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2021)
Soybeans are a very important food requirement in Indonesia, but they often face drought problems. Drought stress causes inefficient nitrogen absorption and makes the stomata close early so photosynthesis is not optimal, resulting in reduced yield. This research was conducted from August 2020 to October 2020 in Demangan village, Sambi sub-district, Boyolali district with polybags in a plastic house. This research method used Factorial Completely Randomized Design (CRD) consisting of two factors and repeated 3 times. The first factor was soil moisture content consisting ie. 100%, 75%, 50%, and 25% of field capacity. The second factor, the growth phase consists of active vegetative, flowering, and seed filling. Observations included the number of branches, number of productive branches, number of trifoliate leaves, the weight of filled pods, and weight of 100 dry seeds. Drought stress reduced the growth and yield of soybean at 25% moisture content in the field capacity of the seed filling phase. The number of branches, the number of productive branches, the number of trifoliate leaves, the weight of filled pods, and the weight of 100 dry seeds decreased with the lowest value.